Cases on practical lessons for economic graduate education - Legeza, Daria; Легеза, Дар'я Георгіївна; Легеза, Дарья Георгиевна (Люкс, 2014)
Article illuminates essence of case method. There are illustrated principles and features of cases in economic education. The structure of case is described.
Keywords: cases; graduate education; interactive method; economic education